Detection of Honey Adulteration by Liquid Chromatography—High-Resolution Mass Spectrometry: Results from an EU Coordinated Action - Viviana Paiano; Andreas Breidbach; Carolin Lörchner; Tereza Ždiniaková; Olivier De Rudder; Alain Maquet; Lourdes Alvarellos; Franz Ulberth (Separations)
Honey, a sweet and nutritious food produced by honeybees, is extensively consumed by humans due to its potential health benefits. Unfortunately, the adulteration of honey with inexpensive sugar syrups is a prevalent issue. Verifying the authenticity of honey is crucial for maintaining its quality and safety standards. The aim of this study was to identify the illicit addition of sugar syrups to honey imported into the European Union (EU). The European Commission’s Joint Research Centre (JRC) has employed different analytical approaches to detect several markers of adulteration in honey; however, this paper mainly focuses on the use of Liquid Chromatography–High-Resolution Mass Spectrometry (LC-HRMS). Two qualitative methods were developed to detect mannose (Man), difructose anhydride III (DFA III), 2-acetylfuran-3-glucopyranoside (AFGP), and oligo-/polysaccharides with degrees of polymerization (DPs) of 6 to 11. Out of the 320 honey samples provided by the authorities of the participating EU Member States, 147 (46%) were suspicious for non-compliance with the EU Honey Directive 2001/110/EC, mostly due to the presence of mannose and oligo-/polysaccharides. As a result, the development and standardization of sophisticated and universally recognized testing procedures will increase the capability of official control laboratories to detect honey adulteration and will serve as a powerful preventive measure against fraudulent practices in the global honey market.